2018
DOI: 10.1007/s00436-017-5744-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bat trypanosomes from Minas Gerais state, Brazil, based on 18S rDNA and Cathepsin-L-like targets

Abstract: Several bat species can be infected by trypanosomes, but there is not much information about which of these parasites infect bats from Triângulo Mineiro and Alto Paranaíba, Minas Gerais state, Brazil, a formerly endemic region for Trypanosoma cruzi, the causative agent of Chagas disease. The aim of this study was to describe, characterize, and identify the presence of trypanosomes in bats. The captured bats (448) belong to four families and to 19 different species. Of those, 37 bats were found to be positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Regarding PCR positivity, the prevalence of trypanosomatids was similar to that observed by other studies in Brazil [3][4], as was the result that in terms of dietary habits most of these bats were nectarivores. It was also demonstrated in this study that the two most common species that circulate in bats in this region are T. c. marinkellei and T.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Regarding PCR positivity, the prevalence of trypanosomatids was similar to that observed by other studies in Brazil [3][4], as was the result that in terms of dietary habits most of these bats were nectarivores. It was also demonstrated in this study that the two most common species that circulate in bats in this region are T. c. marinkellei and T.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the use of the direct parasitological method of microhematocrit revealed frequent positive results for trypanosomatids, as has been demonstrated by other studies [4,28]. It is worth highlighting that the microhematocrit method, in all the field studies carried out by our group, especially in small animals, has shown greater sensitivity or, in certain cases, similar behavior to that of traditional blood culture methods [29].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations